IMPACT OF ANTICOAGULANT THERAPY ON HEMOSTATIC AND INFLAMMATORY MARKERS IN PATIENTS WITH IMMUNE-MEDIATED MICROVASCULAR THROMBOSIS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Immune-mediated microvascular thrombosis (IMMT) is a complex disorder driven by immune dysregulation, leading to microvascular occlusion and necessitating anticoagulant therapy. This study evaluates the impact of anticoagulant therapy on hemostatic parameters (D-dimer, fibrinogen, prothrombin time [PT], activated partial thromboplastin time [APTT]) and inflammatory markers (C-reactive protein [CRP], interleukin-6 [IL-6]) in 45 patients with IMMT. Patients were followed for 12 months, receiving either warfarin or direct oral anticoagulants (DOACs). D-dimer levels decreased significantly (1.5 µg/mL to 0.6 µg/mL, p